Tanggung Gugat Organisasi Persaudaraan Setia Hati Terate atas Perbuatan Melanggar Hukum oleh Anggota dalam Perspektif Hukum Perdata - Bima Alief Saputra; Lintang Yudhantaka (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Persaudaraan Setia Hati Terate (PSHT), as a legal entity, is a legal subject that can be held liable for losses resulting from clashes between its members. This normative legal research analyzes the limits of organizational liability for unlawful acts under Article 1365 of the Civil Code. The results of the study indicate that in addition to the individual responsibility of the perpetrator, the organization can be held accountable under Article 1366 of the Civil Code if proven negligent in its guidance and supervision. The injured party can take litigation or non-litigation routes such as mediation. Strengthening internal governance and clear regulations are needed to ensure legal certainty and protection for the community affected by the actions of the organization's members.